A new type of primitive Cynodont - Brink, A. S. (Bernard Price Institute for Palaeontological Research, 1961)
A very interesting ancestral type of Cynodont is described in reasonable detail from serial sections, graphical figures, and a complete wax model, four times natural size. The form is recognised as a new genus and species, for which the name Scalopocynodon gracilis is proposed. It is the earliest true Cynodont, from the base of the lower Cistecephalus-zone. Although its nearest allies are the somewhat later Silphedestids and Procynosuchids, it has unmistakably very close affinity with the base of the Ictidosuchid-Scloposaurid branch of the Therocephalians. Thus new light is cast on the origin of the Cynodonts and their general relationship with the Therocephalia. The specimen was thought to be a Scaloposaurus before it was decided to subject it to serial grinding.
Main article
Keywords: Cynodont